2016
DOI: 10.15275/rusomj.2016.0104
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-related quality of life in patients with small cell lung cancer: a systematic PubMed review and meta-analysis

Abstract: Abstract:Objective -Symptoms of small cell lung cancer (SCLC), along with the side-effects of treatment interventions (e.g. nausea and vomiting due to cytotoxic drugs), are supposed to influence negatively the health-related quality of life (HRQoL) of the patients. An understanding of the determinants of SCLC patients' HRQoL could help health professionals in clinical decision making, screening and prediction of health outcomes. The aim of this review was to identify the health-related quality of life determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(38 reference statements)
1
1
0
1
Order By: Relevance
“…However, we found that the higher level of knowledge, the compliance rate and utility scores are also increased. This is in accordance with the studies conducted by Kossioris & Karousi,6 in which that the high knowledge of patients on health directly affect the quality of life of patients. Several studies have found a positive correlation between the knowledge with patient adherence in type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we found that the higher level of knowledge, the compliance rate and utility scores are also increased. This is in accordance with the studies conducted by Kossioris & Karousi,6 in which that the high knowledge of patients on health directly affect the quality of life of patients. Several studies have found a positive correlation between the knowledge with patient adherence in type 2 diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, social demographic factors, medications and disease characteristics (complications, comorbidities and prolonged illness) are also associated with quality of life. 6,7 Social demographic factors directly affect the knowledge of patients with type 2 diabetes. 8 Patient's adherence to treatment may also be influenced by social demographic factors of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Demikian juga dengan Status perkawinan, karena dalam menjalani setiap proses perawatan ulkus diabetes memerlukan dukungan dari orang sekitar. Menurut (Kossioris & Karousi, 2015), pasien dengan nilai BMI (Body Massa Index) lebih dari 30 dan menderita ulkus diabetes cenderung memiliki drajat kualitas hidup yang lebih buruk.…”
Section: Pendahuluanunclassified